Null energy condition of dynamical black holes in spatially flat FLRW space-times - Ion I. Cotăescu (European Physical Journal C: Particles and Fields)
Abstract A new identity reported here for the first time is used for studying how the null energy condition can be applied to the models of dynamical black holes proposed recently (Cotăescu in Eur Phys J C 82:86, 2022). It is shown that this condition selects the models with physical meaning whose horizons evolve in accordance with the general black hole theory in frames with null coordinates (Hayward in Phys Rev D 49:6467, 1994).